Carboxylation of Alkenyl Boronic Acids and Alkenyl Boronic Acid Pinacol Esters with CO2 Catalyzed by Cuprous Halide. Issue 19 (12th May 2020) - Hong, Junting; Nayal, Onkar S.; Mo, Fanyang
Abstract : A cuprous halide catalysed carboxylation of alkenyl boronic acids and alkenyl boronic acid pinacol esters under CO2, affording the corresponding α, β‐unsaturated carboxylic acids in good yield, has been developed. The potassium ( E )‐trifluoro(styryl)borate is also compatible with this reaction. This simple and efficient copper(I) catalytic system showed good functional group tolerance. Abstract : Three kinds of alkenyl boron compounds were effectively transformed into the corresponding α, β‐unsaturated carboxylic acids in moderate to high yields through a cuprous halide catalyzed carboxylation with CO2 . The advantages of this method include low cost, mild conditions, simple operation, broad scope, and external ligand free.